The importance of Phobos simulants: a review on our current knowledge - Miranda, Catarina; Patel, Manish; Berberan-Santos, Mário Nuno; Hormigo, Tiago; Correia, Alexandre C. M.; Pedras, Bruno; Martins, Zita (Frontiers in Astronomy and Space Sciences, 2023)
Phobos, a satellite of Mars, was successfully studied by flyby, orbiter, and landing missions to the Red Planet, but several questions remain about its origin, composition, and relationship to Mars. It is suggested that Phobos is either a captured body from the asteroid belt or the outer Solar System (capture scenario), or a consequence of re-accreted ejecta from Mars (in situ formation/giant impact). So far, Phobos has been characterized by its two spectral units - blue and red - with different compositional restrains. The red unit represents most of the surface, while the blue unit is focused on the Stickney crater and surroundings. In the absence of samples returned from this satellite, simulant regolith must be studied to infer various proprieties, and complement in situ studies. To date, there are three simulants of this satellite: Phobos-1C, Phobos Captured Asteroid-1 (PCA-1), and Phobos Giant Impact-1 (PGI-1). Since Phobos may have a Mars-like composition, terrestrial analogues of Mars should also be analysed. The data retrieved from the various assays performed with these planetary field analogues may be used as a database to complement future space missions to Phobos, but, ultimately, the composition of Phobos will have to be analysed by a sample-return mission.